Exponential Stability and Numerical Methods of Stochastic Recurrent Neural Networks with Delays - Shifang Kuang; Yunjian Peng; Feiqi Deng; Wenhua Gao (Abstract and Applied Analysis)
Exponential stability in mean square of stochastic delay recurrent neural networks is investigated in detail. By using Itô’s formula and inequality techniques, the sufficient conditions to guarantee the exponential stability in mean square of an equilibrium are given. Under the conditions which guarantee the stability of the analytical solution, the Euler-Maruyama scheme and the split-step backward Euler scheme are proved to be mean-square stable. At last, an example is given to demonstrate our results.